Penggunaan Zeolit Alam Teraktivasi Sebagai Katalis Pada Proses Esterifikasi Gliserol Dari Produk Samping Biodiesel Menjadi Triacetin - Dwi Yuni Ernawati; Zuchra Helwani; Silvia Reni Yenti (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Glycerol is a byproduct of biodiesel production by transesterification process which generated approximately 10% of the total production of biodiesel. Increasing the amount of glycerol is not accompanied by glycerol treatment process itself. Hence the need for the processing of glycerol into other materials or products that are more economic value. One of them with the process into triacetin. Triacetin can be produced from the reaction of glycerol and acetic acid using an acidic catalyst. Triacetin usefulness pretty much both for food and non-food. The objective of this study was to study the effect of ratio of reactant and consentration of catalyst on glycerol conversion on triacetin. This research was conducted with the reactants ratio 1: 3; 1: 5 and 1: 7, catalyst concentration of 2%, 4%, and 6% of the weight of acetic acid, reaction temperature of 100 °C and reaction time of 4 hours. From the analysis of the results showed that the increase in ratio of esterification of the reactants and catalyst concentration affect the conversion of glycerol into triacetin. The optimal reaction conditions on the reactant ratio of 1: 7 and the concentration of catalyst 4% of the weight of acetic acid with 82.89% conversion rate.Kata kunci: asam asetat, gliserol, optimum, reaktan, triacetin.